Complete mitochondrial genome sequence of golden pompano Trachinotus ovatus. (3rd March 2016) - Sun, Liyuan; Zhang, Dianchang; Guo, Huayang; Jiang, Shigui; Zhu, Caiyan
Abstract: The complete mitochondrial genome of Trachinotus ovatus was determined by the polymerase chain reaction (PCR). The mitogenome is 16, 564 bp long and has the typical vertebrate mitochondrial gene arrangement, including 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and one control region. The overall base composition of mitogenome is estimated to be 29.0% for A, 28.9% for C, 26.2% for T, 15.9% for G, respectively, with a high A + T content (55.2%). With the exception of ND6 and eight tRNA genes, all other mitochondrial genes are encoded on the heavy strand. The control region contains a dinucleotide repeat motif, (AT)5 . This mitogenome sequence would play an important role in population genetics and the molecular taxonomy of T. ovatus .